Comparison of Short-term Outcomes of Percutaneous Coronary Intervention between Young Male and Female Patients with Acute Coronary Syndrome (Bangladesh Heart Journal, 2018)
Background:Young women undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) experience greater short-term adverse events than young men. There is a scarcity of data on the short-term adverse outcomes between young Bangladeshi males and females with ACS undergoing PCI.Objectives: This study was conducted to compare the short-term outcomes of PCI between young males and females presenting with ACS.Methods: This prospective observational study was done in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD) fromApril 2016 to March 2017. 190 young patients with ACS and undergoing PCI were enrolled. They were equally divided into two groups, group I (young females